1967
DOI: 10.1017/s002211206700179x
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of drag in a conducting fluid with an aligned field and large interaction parameter

Abstract: The drag of spheres and disks has been measured in a flow of liquid sodium within an aligned magnetic field. A slightly viscous, strong field limit is discussed and explored experimentally. In this limit the drag coefficient was found to have an asymptotic dependence proportional to the square root of the interaction parameter, the ratio of magnetic to inertial force, independent of body shape. A physical model is presented along with preliminary verification of its basic characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
11
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 7 publications
17
11
0
Order By: Relevance
“…With regard to the magnetic field, the surface pressure at = 90 • (the interface between upstream and downstream regions) increases until N <1, beyond which it decreases. This is in accordance with the experimental findings of Maxworthy [17,19] and Yonas [20]. The pressure at front stagnation point p ( = 0, = 1) decreases until N <1 and then increases.…”
Section: Pressure Fields and Surface Pressuresupporting
confidence: 92%
See 1 more Smart Citation
“…With regard to the magnetic field, the surface pressure at = 90 • (the interface between upstream and downstream regions) increases until N <1, beyond which it decreases. This is in accordance with the experimental findings of Maxworthy [17,19] and Yonas [20]. The pressure at front stagnation point p ( = 0, = 1) decreases until N <1 and then increases.…”
Section: Pressure Fields and Surface Pressuresupporting
confidence: 92%
“…The total drag coefficient C D is found to vary with for 2. The linear dependence with √ N of drag coefficient is reported experimentally by Maxworthy [19], Yonas [20] and Josserand et al [18]. There is a non-monotonic decrease in drag coefficient with R m for low magnetic fields until N ≈ 1 (Figure 15(c)).…”
Section: Drag Coefficientsupporting
confidence: 64%
“…The drag coefficients as a function of interaction parameter N are shown in Figure 4 for Re ¼ 200. It is found that the drag coefficient decreases up to N 1 and then increases with N. Such a type of variation is reported in the literature [19,20]. …”
Section: Resultssupporting
confidence: 71%
“…Coincidentally, the magnetohydrodynamic modification to the drag coefficient generally is larger for motion perpendicular to the magnetic field compared with that for motion parallel to the magnetic field. [7,8,[10][11][12] The experimental [16] and computational [18] results discussed briefly in the introduction provide confidence that for a bubble motion perpendicular to the magnetic field, the magnetohydrodynamic modifications to the drag coefficient of rigid spheres can be used. Experimental work on rigid spheres [12] reports within the range 17:6 Re 332 and N 2:5 Â 10 3 a dependence…”
Section: A Magnetohydrodynamically Modified Dragmentioning
confidence: 99%
“…For rigid spherical objects, significant theoretical, [7][8][9] experimental, [10][11][12] and computational [13][14][15] work has been reported. Recently, experiments with deformable bubbles have been performed [16,17] showing that in this case, a magnetic field modifies the drag coefficient as well.…”
Section: Introductionmentioning
confidence: 99%